Gendered district poverty profiles and poverty monitoring Kabarole, Masaka, Pallisa, Rakai and Tororo districts, Uganda - Helle Munk Ravnborg; Jannik Boesen; Anne Sørensen; Zarupa Akello; Bernard Bashaasha; Sarah Kasozi; Michael Kidoido; Veronica Wabukawo (Danish Institute for International Studies (DIIS), 2004)
The overall objective of the Danida supported Agricultural Sector Programme Support (ASPS) in Uganda is to improve the conditions for the poorest part of the population and contribute to reduce gender-based inequalities in Uganda in general and in the pilot focus districts in particular. Late in 2000, Danida asked Department of Agricultural Economics, Makerere University, Kampala, and Centre for Development Research, Copenhagen, to form an external task group with the purpose of monitoring the gender and poverty impact of the ASPS. The present Working Paper presents a slightly revised version of one of the reports that have been the response to this task.1 The Paper presents gendered district poverty profiles for the five ASPS pilot districts, i.e. Kabarole, Masaka, Pallisa, Rakai and Tororo districts, as well as the methodology for developing these profiles. It depicts and compares the situation of the `betteroff', the `less poor' and the `poorest' households in the five districts according to a number of dimensions, which local people themselves have identified as important when describing poverty and well-being in their communities. In addition, the report analyses the aspect of equality and inequality in gender relations within the household. Based on women's own perceptions of female well-being, three levels of equality in gender relations are distinguished and related to household poverty. These profiles are the district baselines against which the gender and poverty impact of the ASPS can be monitored in the future. Finally, the report makes a very preliminary attempt at analysing the outcomes, including both the households reached and the resulting behavioural changes achieved through the various interventions supported by the ASPS components. This is related both to poverty levels, gender relations and differences between districts. The Paper concludes by outlining how the analysis should be undertaken when the exercise of developing gendered district poverty profiles is repeated three to four years later as part of ASPS impact monitoring.
Keywords: 330; Armut; Regionale Disparität; Uganda